Three-dimensional printed models as an effective tool for the management of complex congenital heart disease - Capellini, Katia; Ait-Ali, Lamia; Pak, Vitali; Cantinotti, Massimiliano; Murzi, Michele; Vignali, Emanuele; Fanni, Benigno Marco; Clemente, Alberto; Celi, Simona; Gasparotti, Emanuele (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: 3D printed models are widely used in medical field for surgical and interventional planning. In the context of complex cardiovascular defects such as pediatric congenital heart diseases (CHDs) the adoption of 3D printed models could be an effective tool to improve decision making. In this paper, an investigation was conducted into the characteristics of 3D printed models and their added value in understanding and managing complex pediatric congenital heart disease, also considering the associated cost.Methods: Volumetric MRI and CT images of subjects with complex CHDs were retrospectively segmented and the associated 3D models were reconstructed. Different 3D printing technologies and materials were evaluated to obtain the 3D printed models of cardiac structures. An evaluation of time and costs associated with the 3D printing procedure was also provided. A two-level 3D printed models assessment was carried out to investigate the most suitable 3D printing technology for the management of complex CHDs and the effectiveness of 3D printed models in the pre-surgical planning and surgical strategies simulations.Results: Among the different techniques, the selective laser sintering resulted the most suitable due to its reduced time and cost and for the positive clinical feedback (procedure simulation, surface finish and reproduction of details).The adoption of 3D-printed models contributes as effective tool in the management of complex CHDs enabling planning and simulations of surgical procedures in a safer way.